Evidence for involvement of multiple forms of cytochrome P-450 in aflatoxin B1 metabolism in human liver. - Forrester, L M (1990)
Liver cancer is a major cause of premature death in many areas of Africa and Asia and its incidence is strongly correlated with exposure to aflatoxin B1 (AFB1). Because AFB1 requires metabolic activation to achieve a biological response, there is a need for detailed knowledge of the mechanism of activation to assess individual risk. We have carried out an extensive study using a total of 19 human liver samples to determine the individual variability in the metabolism of the toxin to mutagenic or detoxification products and to identify the specific cytochrome P-450 forms involved in these processes. Metabolism to the toxic 8,9-epoxide or to products mutagenic in the Ames test was found to exhibit very large individual variation. The rates of metabolic activation were highly correlated with both the level of proteins of the P450IIIA gene family and with the total cytochrome P-450 content of the microsomes. In agreement with this, antibodies reacting with P450IIIA proteins were strong inhibitors of both the metabolism and mutagenicity in the majority of the samples. However, the inhibition varied between 50% and 100%. The expression of a protein in the P450IIC gene family also correlated with AFB1 metabolism and mutagenicity. This result therefore indicated the involvement of cytochromes other than P450IIIA in the activation of AFB1 by human liver microsomes. This hypothesis was strongly supported by the finding that antibodies to P450IA2 and P450IIA1 were also effective inhibitors of metabolism in many of the samples. These data demonstrate that, although P450IIIA probably plays an important role in AFB1 activation, several other cytochrome P-450 forms have the capacity to activate the toxin. Similar considerations apply to detoxifying metabolism to aflatoxin Q1 and aflatoxin M1. The levels of expression of many of the forms of cytochrome P-450 involved in AFB1 metabolism are known to be highly sensitive to environmental factors. This indicates that such factors will be an important determinant in individual susceptibility to the tumorigenic action of AFB1.